Systemic treatment of seborrheic dermatitis with retinol palmitate - O. V. Kalinina; V. I. Albanova; T. A. Belousova; V. I. Nozdrin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The goal of the study. Evaluating of the effectiveness of treatment of men with a diagnosis «Seborrheic dermatitis of the scalp» by the system using of retinol palmitate. Material and methods. 36 patients every day for 2 months received overnight per os 200000 ME of retinol palmitate, and in the comparison group (39 people) antiseborrheic shampoos have been used. The dynamics of severity of skin oiliness, pruritis, erythema, peeling, infiltration, excoriations has been evaluated in points. Before and after the treatment a histological and morphometric study of biopsy material from the affected areas has been carried.The terms of relapses have been set. Results. Retinol palmitate treatment efficiency - 91.7%, antiseborrheic shampoos - 84.6%. Along with the regression of symptoms of the disease in both groups after retinol palmitate treatment significantly declined oiliness of skin; the sizes of sebaceous glands acini and the presence of differentiated sebocytes, the squares of lymphocytic-macrophage clusters in the dermis, the number of keratinocytes with vacuolated cytoplasm have been reduced. Relapses of the disease during a year occured more rare - in 21 patients out of 32 (in the comparison group- in 25 out of 31) and at a later date (in the first 3 months in 2 patients out of 32, in comparison group in 10 out of 31). Identified effects were due to the action of retinol palmitate on the morphogenesis of the sebaceous glands.